2002
DOI: 10.1055/s-2002-35296
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Capsule Video Endoscopy: A New Diagnostic Method for Aortoduodenal Fissure

Abstract: Figure 2 Meanwhile, wireless capsule video endoscopy was carried out to confirm the diagnosis in this patient, owing to the high risk of the intervention. Surprisingly, the wall of the small intestine in the ascending duodenum had been replaced by the Dacron prosthesis, producing the imaging appearance shown here. This unexpected finding was confirmed during open abdominal surgery. Figure 1A 66-year-old man with a history of aortobifemoral bypass 5 years previously was admitted to our hospital with abdominal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
1
3
0
4
Order By: Relevance
“…In view of the associated significant mortality (22-100%) [2,3], early recognition of an AEF is paramount. To the best of our knowledge, this is the first report of a jejunal AEF identified by SBCE and confirms the usefulness of capsule endoscopy in providing corroborative evidence for diagnosis [4], especially where the AEF lies beyond the duodenum. …”
supporting
confidence: 75%
“…In view of the associated significant mortality (22-100%) [2,3], early recognition of an AEF is paramount. To the best of our knowledge, this is the first report of a jejunal AEF identified by SBCE and confirms the usefulness of capsule endoscopy in providing corroborative evidence for diagnosis [4], especially where the AEF lies beyond the duodenum. …”
supporting
confidence: 75%
“…50 The use of F18-fluorodeoxyglucose-positron emission tomography/CT (FDG-PET/CT) has also been described as a potent diagnostic tool for ADF. 52 Gonzá lez-Suá rez et al 53 reported the use of wireless capsule video endoscopy for depicting an ADF.…”
Section: Discussionmentioning
confidence: 99%
“…In vielen Fallberichten konnte die Endoskopie die Diagnose nicht stellen [5,9,11,16]; in einer Studie von Pipinos et al wird die Sensitivität der Ösophagogastroduodenoskopie gar mit nur 25 % angegeben [17]. Zur Push-Enteroskopie und zur Doppelballon-Enteroskopie liegen keine Daten zu aortoenterischen Fisteln vor; eine Kasuistik beschreibt die mögliche Rolle der Kapselendoskopie [18]. Wegen der Problematik der endoskopischen Diagnosestellung empfehlen manche Autoren die Computertomographie als primäre diagnostische Methode [11]; Perks et al berichteten kürzlich über die computertomographische Diagnose aortointestinaler Fisteln bei 3 Patienten [18].…”
Section: Kasuistikunclassified
“…Zur Push-Enteroskopie und zur Doppelballon-Enteroskopie liegen keine Daten zu aortoenterischen Fisteln vor; eine Kasuistik beschreibt die mögliche Rolle der Kapselendoskopie [18]. Wegen der Problematik der endoskopischen Diagnosestellung empfehlen manche Autoren die Computertomographie als primäre diagnostische Methode [11]; Perks et al berichteten kürzlich über die computertomographische Diagnose aortointestinaler Fisteln bei 3 Patienten [18]. In zwei der von uns dargestellten Fälle war computertomographisch die Nachbarschaft zwischen Duodenum und Aortenprothese bzw.…”
Section: Kasuistikunclassified